Answer:
The polynomials that represents the answer is -2x² - x + 14 ⇒ a
Explanation:
Let us solve the question
∵ The expression is 3(x + 2) - 2(x² + 2x - 4)
→ Multiply each bracket by the number before it
∵ 3(x + 2) = 3(x) + 3(2)
∴ 3(x - 2) = 3x + 6
∵ 2(x² + 2x - 4) = 2(x²) + 2(2x) + 2(-4)
∴ 2(x² + 2x - 4) = 2x² + 4x + (-8)
→ Remember (+)(-) = (-)
∴ 2(x² + 2x - 4) = 2x² + 4x - 8
∴ 3(x + 2) - 2(x² + 2x - 4) = (3x + 6) - (2x² + 4x - 8)
→ Multiply the (-) by all the terms in the 2nd bracket
∴ 3(x + 2) - 2(x² + 2x - 4) = 3x + 6 - 2x² - 4x + 8
→ Add the like terms
∵ 3(x + 2) - 2(x² + 2x - 4) = -2x² + (3x - 4x) + (6 + 8)
∴ 3(x + 2) - 2(x² + 2x - 4) = -2x² + (-x) + 14
∴ 3(x + 2) - 2(x² + 2x - 4) = -2x² - x + 14
∴ The polynomials that represents the answer is -2x² - x + 14